THE EVOLUTION OF AL-FAHSHĀ’ AND AL-MUNKAR IN THE MODERN AND CONTEMPORARY ERA: AN ECO-SUFI SEMIOTIC PERSPECTIVE - Putri, Amelia (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2024)
This study aims to expand the understanding of the concepts of fahsyā’ and munkar through an eco-sufistic perspective using Charles Sanders Peirce’s semiotic approach. Traditionally, these two terms have been understood in moral and social contexts. However, this research offers a reinterpretation that broadens the scope of both concepts. Fahsyā’ is understood as environmental damage caused by irresponsible human activity, while munkar represents internal corruption, such as egoism and behavior that contradicts human nature. Through Charles Sanders Peirce’s triadic theory (sign, object, and interpretant), this study explores Quranic verses to connect the spiritual and ecological dimensions of both concepts. The results show that fahsyā’ reflects the destructive impact of humans on nature, arising from unchecked greed and exploitation. On the other hand, munkar reflects internal dissonance that disrupts the harmony of humans with themselves, society, and their environment. This perspective integrates Sufistic ethics with environmental sustainability issues, emphasizing that ecological awareness is an integral part of Islamic teachings. This approach not only enriches Quran-based ecological discourse but also highlights how Sufism can inspire the development of holistic behaviors that maintain the balance of nature. This study makes a significant contribution by expanding the interpretation of Quranic verses relevant to contemporary ecological issues, while strengthening the role of Islamic spirituality in addressing the pressing challenges of environmental degradation in the modern era.